Segurança de ziv-aflibercepte intravítreo - Dias, João Rafael de Oliveira [UNIFESP] (2017)
Purpose: 1. To evaluate the viability of ARPE-19 human retinal pigment epithelial cells after exposure to ziv-aflibercept 12.5 and 25 mg/mL; 2. To evaluate the safety of intravitreal ziv-aflibercept in an experimental rabbit model; 3. To evaluate the clinical and electrophysiological safety of intravitreal ziv-aflibercept in patients with exudative age-related macular degeneration. Methods: In the first study, the ARPE-19 cells were exposed for 10 minutes and 24 hours to the two concentrations of ziv-aflibercept; balanced salt solution (BSS) and culture mean were used as controls. The effect of ziv-aflibercept on the cellular viability was analyzed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay (MTT). All experiments were performed in triplicate and repeated three times. In the second study, pigmented rabbits (chinchilla breed) underwent a fundus examination, fundus imaging, full-field electroretinography (ERG), and optical coherence tomography (OCT) at baseline and 24 hours or 7 days after an intravitreal injection of 0.05 mL of ziv-aflibercept (25 mg/mL; n=9) or aflibercept (40 mg/mL; n=9) in the right eye and BSS in the left eye. Serum, aqueous, and vitreous specimens were obtained at baseline and 24 hours or 7 days after the intravitreal injection for osmolality analysis. After euthanasia and enucleation, both eyes of each animal were analyzed by light microscopy and transmission electron microscopy 24 hours or 7 days after the intravitreal injections. In the third study, patients with unilateral exudative age-related macular degeneration received three monthly intravitreal injections of 0.05 mL of ziv-aflibercept (25 mg/mL) followed by as-needed treatment. The safety of intravitreal ziv-aflibercept was determined by the results of full-field ERG, and the efficacy was determined by the best-corrected visual acuity measurements, OCT imaging, and multifocal ERG. The safety and efficacy parameters were evaluated at 26 and 52 weeks. Results: Neither the 12.5 or 25 mg/mL concentrations of ziv-aflibercept reduced the cellular viability in the MTT assay compared to the controls. In the experimental rabbit study, all eyes had normal fundus examinations, OCT imaging, and full-field ERGs 24 hours or 7 days after the intravitreal injection of 0.05 mL of ziv-aflibercept (25 mg/mL), aflibercept (40 mg/mL) or BSS. There were no significant changes in the mean serum, aqueous, and vitreous osmolalities. Light microscopy and transmission electron microscopy showed no major signs of toxicity compared to aflibercept. In the third study, 15 patients completed the 26-week follow-up and 14 patients completed the 52-week follow-up. Intravitreal ziv-aflibercept injections significantly improved the visual acuity, increased the multifocal ERG amplitudes within the central 0o to 15o degrees, and decreased the central macular thickness and total macular volume seen on OCT imaging 26 weeks after the intravitreal ziv-aflibercept injections. No signs of retinal toxicity were seen in full-field ERGs and no ocular or systemic adverse events developed 26 weeks after treatment with intravitreal ziv-aflibercept. A comparison between baseline and 52 weeks showed an increase in the mean visual acuity, an increase in multifocal ERG amplitudes within the central 5o, and significant reductions in the central macular thickness and total macular volume. There was a decrease in the mean amplitude of the a-wave, an increase in the mean implicit time of the a-wave in the full-field ERG, and a decrease in the mean amplitude of the 30-Hz flicker, which did not differ significantly when the treated eye was compared to the fellow eye. One patient presented with anterior segment and vitreous inflammation 4 days after one injection, the signs and symptoms of which resolved completely after treatment with topical and systemic steroids. One patient developed posterior subcapsular cataract during the follow-up. Conclusions: Neither concentrations of ziv-aflibercept reduced the cellular viability compared to controls, and the intravitreal injection of ziv-aflibercept 25 mg/mL was safe in the rabbit retina. The human study showed improvements in the visual acuity 26 and 52 weeks after the beginning of the treatment with intravitreal ziv-aflibercept. The central macular thickness and total macular volume improved 26 and 52 weeks after the beginning of the treatment with intravitreal ziv-aflibercept. No findings suggested retinal toxicity on full-field ERG 26 and 52 weeks after the beginning of the treatment with intravitreal ziv-aflibercept.